DEVELOPMENT OF LIVESTOCK FARMING IN THE LVIV REGION AT THE TURN OF THE CENTURY (INNOVATIVE ECONOMY, 2024)
Shulskyi M.H., Ramskyi I.O. DEVELOPMENT OF LIVESTOCK FARMING IN THE LVIV REGION AT THE TURN OF THE CENTURYPurpose. The aim of the article is to study the state of livestock development in the economic formations of Lviv region with an emphasis on the functioning of this industry in households.Methodology of research. The collected data was processed using various methods of economic research, namely: historical (the phenomenon of livestock development in households is considered in historical retrospect); dialogue (the processes of livestock development are studied from the point of view of forming the author's questions, and the answers are from the relevant source); systemic-structural, abstract and logical (all structural components of this study are presented in a certain logical and abstract sequence). All research processes were closely linked from the standpoint of their dialectical development.Findings. A study of the development of livestock industries in Lviv region was conducted with a focus on their functioning in households. The essence of the main terms presented in the statistical materials (Table 1) is detailed and their interpretation is specified, the availability of livestock and the volume of livestock production both in general in the Lviv region and in the context of specific forms of management is given (Table 3). The results of the study are accompanied and reflected in specific digital indicators.Originality. It was established that in order to specify the contribution of existing forms of management in agriculture, it is advisable to present farming separately, rather than reflecting the activities of farmers with indicators of other forms of management. It was substantiated that in order to overcome the negative consequences of the decrease in the number of farm animals in agricultural enterprises, it is advisable to increase the cultivation of animals directly in the studied farms and to purchase highly productive animals from outside.Practical value. The implementation of the outlined proposals and recommendations should involve not only the economic entities themselves, but also the state authorities. Their interaction should be reflected in the development of a comprehensive programme for solving urgent problems arising from both the results of the study on the above topic and other research results.Key words: animal husbandry, households, development, era, reforms.
Keywords: animal husbandry; households; development; era; reforms.